Urban development and the importance of chamfers in corners lots: the case of Juína municipality, Mato Grosso State - Araújo, Rildo Vieira de; Lima, Halan Faria; Galvão, Leonice Barros; Costa, Reginaldo Brito da (Interações, 2019)
The study aimed at identifying and analyzing urban development in the city of Juína, MT, focusing on corner lots chamfers and their importance for the visibility of pedestrians and vehicles. It was found that corners and their respective chamfers did not present a pattern, whereas in others, there were no bevels. This reality occurs in many municipalities in Brazil.